Perceived Body Image in Psychology Students from Yucatán, Mexico - Guadalupe Simanga Ivett Robles Hernández; Ricardo Gumaro Molina Jacquez; Omar Benjamín Solis; María Del Carmen Zueck Enríquez; Humberto Blanco Vega; Martín Alonso González Hernández; Fernando Mondaca Fernández; Carolina Jiménez Lira (European Scientific Journal, ESJ, 2020)
Body image is an important psychological component related to current health issues such as eating disorders. It is also related to social, peer, and family pressure, by which men and women are affected to different degrees. Thus, the goal of the present research was to compare the perceived body image profiles in Mexican psychology students. The total sample consisted of 271 students; 139 women and 132 men from the Autonomous University of Yucatán, ages ranged between 17 and 28 years. The approach adopted in this research was quantitative with a descriptive survey like design. The results from the multivariate analyses of variance followed up by univariate analyses of variance, show that men report a better perceived body image than women on the factors behaviors oriented towards maintaining the physical shape (F = 317.008, p < .001) and care of physical aspect (F = 19.939, p < .001); and no significant differences on the factors of subjective importance of corporality and self-assessed physical attractiveness. These results show that in general men, in comparison to women show lower levels of dissatisfaction with their body image. Regardless, it is necessary that more research on the matter be developed given that the topic transcends the scope of the present research.